Commonwealth Responsibility and Cold War Solidarity Australia in Asia, 1944-74 - Halvorson, Dan (ANU Press, 2019)
Australia's engagement with Asia from 1944 until the late 1960s was based on a sense of responsibility to the United Kingdom and its Southeast Asian colonies as they navigated a turbulent independence into the British Commonwealth. The circumstances of the early Cold War decades also provided for a mutual sense of solidarity with the non‑communist states of East Asia, with which Australia mostly enjoyed close relationships. From 1967 into the early 1970s, however, Commonwealth Responsibility and Cold War Solidarity demonstrates that the framework for this deep Australian engagement with its region was progressively eroded by a series of compounding, external factors: the 1967 formation of ASEAN and its consolidation by the mid-1970s as the premier regional organisation surpassing the Asian and Pacific Council (ASPAC); Britain's withdrawal from East of Suez; Washington's de‑escalation and gradual withdrawal from Vietnam after March 1968; the 1969 Nixon doctrine that America's Asia-Pacific allies must take up more of the burden of providing for their own security; and US rapprochement with China in 1972. The book shows that these profound changes marked the start of Australia's political distancing from the region during the 1970s despite the intentions, efforts and policies of governments from Whitlam onwards to foster deeper engagement. By 1974, Australia had been pushed to the margins of the region, with its engagement premised on a broadening but shallower transactional basis.